Solve the system by the elimination method.
-2x + y + 6 = 0
2x + y - 8 = 0
When you eliminate x, what is the resulting equation?
2y = 2
2y = -2
y = -2

Question

Asked 12/17/2015 7:10:37 PM

Updated 12/27/2015 4:56:50 AM

1 Answer/Comment

Flagged by arel [12/27/2015 4:56:01 AM]

s

Question

Asked 12/17/2015 7:10:37 PM

Updated 12/27/2015 4:56:50 AM

1 Answer/Comment

Flagged by arel [12/27/2015 4:56:01 AM]

Rating

8

Solve the system by the elimination method. -2x + y + 6 = 0 2x + y - 8 = 0 When you eliminate x, the resulting equation is 2y = 2.

-2x + y + 6 + 2x + y - 8 = 0;

2y - 2 = 0;

2y = 2

-2x + y + 6 + 2x + y - 8 = 0;

2y - 2 = 0;

2y = 2

Added 12/27/2015 4:56:50 AM

This answer has been confirmed as correct and helpful.

Find the equation of a line given the point and slope below. Arrange your answer in the form y = mx + b, where b is the constant.
(-6, 1)
m = 6

Question

Updated 12/18/2015 5:13:34 PM

1 Answer/Comment

The equation of a line given the point and slope below. Arrange your answer in the form y = mx + b, where b is the constant. (-6, 1) m = 6,the equation is y = 6x + 37.

y - 1 = 6(x + 6);

y = 6x + 36 + 1;

y = 6x + 37

y - 1 = 6(x + 6);

y = 6x + 36 + 1;

y = 6x + 37

Added 12/18/2015 5:13:34 PM

This answer has been confirmed as correct and helpful.

The y-intercept of the line whose equation is 2x + y = 4 is

Question

Updated 2/1/2018 11:58:02 PM

1 Answer/Comment

The y-intercept of the line whose equation is 2x + y = 4 is 4.

2x + y = 4 ;

y = -2x + 4

2x + y = 4 ;

y = -2x + 4

Added 2/1/2018 11:58:02 PM

This answer has been confirmed as correct and helpful.

Find the equation of a line with the given points. (Put your answers in the form y = mx + b.)
(7, 2)
(4, 8)

Question

Updated 12/27/2015 5:09:50 AM

1 Answer/Comment

The equation of a line with the given points. (Put your answers in the form y = mx + b.) (7, 2) (4, 8),the equation is y = -2x + 16.

slope = (8 - 2)/(4 - 7) = -2;

y - 2 = -2(x - 7);

y = -2x + 14 + 2

y = -2x + 16

slope = (8 - 2)/(4 - 7) = -2;

y - 2 = -2(x - 7);

y = -2x + 14 + 2

y = -2x + 16

Added 12/27/2015 5:09:50 AM

This answer has been confirmed as correct and helpful.

Solve the system by the elimination method.
2x + 3y - 10 = 0
4x - 3y - 2 = 0
When you eliminate y, what is the resulting equation? **Weegy:** 2x^2 - 4x + 6 = 0 is in general form. TRUE. (More)

Question

Updated 12/27/2015 4:59:18 AM

1 Answer/Comment

Solve the system by the elimination method. 2x + 3y - 10 = 0 4x - 3y - 2 = 0 When you eliminate y,the resulting equation is 6x = 12.

2x + 3y - 10 + 4x - 3y - 10 - 2 = 0;

6x - 12 = 0;

6x = 12

2x + 3y - 10 + 4x - 3y - 10 - 2 = 0;

6x - 12 = 0;

6x = 12

Added 12/27/2015 4:59:18 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [12/27/2015 10:23:51 AM], Rated bad by jeifunk, Rated good by jeifunk, Rated good by jeifunk

One number is twice another number and their sum is 36.
Which system of equations represents the word problem?
2x + y = 36 and x + y = 36
x + y = 36 and y = 2x
y = 2x and 2x + y = 36'

Question

Updated 12/22/2015 9:11:21 PM

1 Answer/Comment

33,115,901

questions answered

There are no comments.